2013
DOI: 10.1371/journal.pgen.1003927
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Tuning of Protein Expression Levels of a Positively Autoregulated Two-Component System

Abstract: Cellular adaptation relies on the development of proper regulatory schemes for accurate control of gene expression levels in response to environmental cues. Over- or under-expression can lead to diminished cell fitness due to increased costs or insufficient benefits. Positive autoregulation is a common regulatory scheme that controls protein expression levels and gives rise to essential features in diverse signaling systems, yet its roles in cell fitness are less understood. It remains largely unknown how much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…It is not uncommon for TCSs to tune expression of genes. For example, in Salmonella enterica, PhoPQ tunes expression of the effector steA during osmotic stress, and PhoBR tunes expression of itself in E. coli according to environmental phosphate concentrations (69,70). If CvsSR tunes expression of hrpRS, then it is conceivable that deletion of cvsS or cvsR may cause only subtle changes T3SS and T3E deployment that do not affect the HR but could still influence pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is not uncommon for TCSs to tune expression of genes. For example, in Salmonella enterica, PhoPQ tunes expression of the effector steA during osmotic stress, and PhoBR tunes expression of itself in E. coli according to environmental phosphate concentrations (69,70). If CvsSR tunes expression of hrpRS, then it is conceivable that deletion of cvsS or cvsR may cause only subtle changes T3SS and T3E deployment that do not affect the HR but could still influence pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This remarkable, but not perfect, homeostasis of Pho system output strongly suggests that the observed response was nearly optimal. The convergence of Pho responses from different starting points is particularly striking because Gao and Stock previously also demonstrated that the autoregulated amounts of PhoRB signaling proteins generated under conditions of various degrees of P i starvation provide optimal fitness (9).…”
mentioning
confidence: 99%
“…The pho response exhibits just such heterogeneity in the artificial circumstance represented by cells that lack PhoR and activate PhoB by inefficient cross talk from a nonpartner sensor kinase (14). On the other hand, when E. coli bacteria with the wild-type PhoRB system are starved once for P i , the population response is homogeneous and bistability is not seen (9). What happens with a more complex exposure history?…”
mentioning
confidence: 99%
“…different environmental conditions (1)(2)(3). The ever-changing environments constantly challenge cells to optimize strategies to prevail under fluctuating conditions.…”
mentioning
confidence: 99%
“…It has been demonstrated that different levels of PhoBR under different Pi conditions provide near-maximal fitness under the respective conditions. The importance of this was underscored by the finding that challenging cells with unfavorable PhoBR levels led to diverse homeostatic efforts to mediate optimal expression levels through acquisition of mutations (3). Maintaining expression optimality appears to be a strong evolutionary force to select the positive autoregulatory scheme for adaptation to different Pi conditions.…”
mentioning
confidence: 99%